Comparative Analysis Of Nucleic Acid Residues In Core Streptavidin Using Three Isolation Techniques - Alias, Nurul Nadia Mohamad (2024)
Recombinant core streptavidin (cSAV) is a truncated non-glycosylated tetrameric SAV which has been widely utilised in a wide range of biotechnological applications. Due to cSAV commercial importance, recombinant cSAV has been extensively produced using expression host system such as Escherichia coli to high expression level. Nevertheless, accumulation of cSAV in high levels results in the formation of insoluble non-functional inclusion bodies (IBs) which requires efficient downstream processing steps to overcome. This process involves isolation of IBs from cell lysates through combination of cell disruption techniques, multiple centrifugation steps, IBs solubilization and refolding to acquire correctly refolded cSAV. However, during IBs preparation, presence of cellular contaminants such as residual nucleic acids is inevitable and can affect subsequent refolding process. Hence, in this study, the IBs isolation process from our previous group (Process A) was improved to obtain high quality cSAV IBs in an effort to attain refolded cSAV with minimal contaminants. The improvements were enhanced with the incorporation of quantitative polymerase chain reactions (qPCR) for residual DNAs monitoring. By employing combined cell disruption approaches such as extensive sonication (Process B) and addition of benzonase nuclease (Process C), cSAV IBs with 99% removal of residual DNAs were achieved. A 10% increment of cSAV refolding yield (72%) and 83% reduction of residual DNAs from refolding of 1 mg cSAV IBs were observed under extensive sonication. Despite perceiving the least residual DNAs, refolding of cSAV was found not affected and the activity of refolded cSAV was not compromised.